Peran Masyarakat Desa Manggung dalam Pengawasan Dana Desa - Handayani, Rispa; Deviani, Deviani (Wahana Riset Akuntansi, 2024)
AbstractPurpose – This research aims to contribute to literature and evaluation for related parties by finding out the role of the Manggung Village community in monitoring village funds  Design/methodology/approach – This research is qualitative research with a case study approach. Data was collected through interviews and Focus Group Discussions with BPD member communities, self-help member communities, Musrenbang member communities and pure communities with a total of 32 informants.Findings – The research results provide an overview of the accountability stages where the information stage illustrates that there are limitations in information publication and some information publications are only for community groups that are pro towards the Village Government, making the information provided a mere formality. The discussion stage showed that the intensity of discussions between village community representatives and the Village Government was high, but the quality of the discussions was felt to be low. Some finalization of deliberation results were only represented by certain communities who ended up in a different program than before the finalization. Meanwhile, the provision of consequences by village communities is relatively low. The contributing factor is that people do not trust community representatives and audit bodies because they are seen as working together. A family system that is still strong reduces the provision of consequences. And the public also does not understand the mechanisms and complaints services for irregularities found.Originality/value – This research provides a clearer picture than previous research, because there are differences in cases and data collection methods using Focus Group Discussions which reveal the practice of creating accountability at the Village Government level. Education and evaluation not only for the community but also for the village government.Research limitations/implications – This research is not free from shortcomings and limitations, where this research only adds a few informants from previous research. Research informants described the existence of pros and cons which made it difficult to draw conclusions from the interview results. The need for additional data from observation and documentation to support research results.